O computador no ensino-aprendizagem: sua presença e as representações de professores e gestores da rede pública - Nascimento, Milton Andrade do (2008)
This study aims at (1) describing and interpreting the presence of computers in the teaching-learning process taken as a phenomenon of lived experience; and at (2) identifying the representations public school teachers and managers have about the use of such a machine. As its ultimate goal, this investigation also aims at gathering input for the design and future implementation of a teachers technological education course. This research is theoretically based on the notion of representations (Freire & Lessa, 2003); on discussions about learning mediated by computers from a socio-interactional perspective (Vygotsky, 1934/1998, 1934/2000); on concepts of literacy in face-to-face (Freire, 1990; Tfouni, 1988, 2006) and in digital environments (Sampaio & Leite, 1990); on questions regarding teachers education in the digital society, emphasizing digital inclusion and possible roles carried out by educators in contexts mediated by technological tools (Kenski, 2003, 2007; Valente 2005; Pellanda, Schlunzen & Schlunzen Junior, 2005; Moran, 2007). The methodological approach is the hermeneutic-phenomenological one (Ricouer, 1986/2002; van Manen, 1990; Freire, 2006). The research context was a public school, located in the East area of São Paulo city. The textual registers were collected through questionnaires given to participants in a printed or e-mail format. The research comprised three moments: twenty teachers and four managers took part in the first; twelve teachers were enrolled in the second; and three managers participated in the third moment. The outcomes indicated that teachers and mangers share some similar representations. However, when confronted, teachers mention the lack of specific courses directed towards technological skills, as well as the lack of technical support in schools; while managers emphasize the lack of teachers technological skills as a relevant obstacle. By interpreting the presence of computers in the teaching-learning process, the study provides the bases to claim that knowledge, facilities, and difficulties are the themes that constitute such a phenomenon of lived experience